2021
DOI: 10.1101/2021.02.11.430840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Different trajectories of polyploidization shape the genomic landscape of theBrettanomyces bruxellensisyeast species

Abstract: Polyploidization events are observed across the tree of life and occurred in many fungi, plant and animal species. Polyploidy is thought to be an important source of speciation and tumorigenesis. However, the origins of polyploid populations are not always clear and little is known about the precise nature and structure of their complex genome. Using a long-read sequencing strategy, we sequenced a large number of isolates from the Brettanomyces bruxellensis yeast species, which is found in anthropized environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Hybridization is a process common to the life history of many organisms and rapidly generates genomic diversity (14,79,80). Even though new hybrids tend to exhibit a low spore fertility, natural hybridizations have played an essential role in the diversification and evolution of the genome of many fungal, plant, and animal species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridization is a process common to the life history of many organisms and rapidly generates genomic diversity (14,79,80). Even though new hybrids tend to exhibit a low spore fertility, natural hybridizations have played an essential role in the diversification and evolution of the genome of many fungal, plant, and animal species.…”
Section: Discussionmentioning
confidence: 99%
“…The diploid organisms (or those with a higher ploidy) are usually heterozygous for many of these genetic variants across the genome. Nevertheless, a large number of studies have pointed out that regions of the genome can frequently become homozygous for these polymorphisms during mitotic divisions (7)(8)(9)(10)(11)(12)(13)(14)(15). These loss of heterozygosity (LOH) events result from the transfer of information from one homologous chromosome to the other, primarily a consequence of mitotic recombination, among other mechanisms (16).…”
Section: Introductionmentioning
confidence: 99%
“…This large population study allowed the identification of different genetic subpopulations within B. bruxellensis, which were subsequently validated and refined by whole genome sequencing approaches (Eberlein et al, 2021;Gounot et al, 2020;Serra Colomer, Chailyan, et al, 2020;Table S1). At least six subgroups can now be considered, either diploid (two groups) or triploid (four groups; Figure 1b).…”
Section: Population Structure Of Brettanomyces Bruxellensismentioning
confidence: 99%
“…Over the past decade, several de novo assemblies have been published with increasing quality (Table 1), in particular thanks to the combination of long-read sequencing (e.g., Oxford Nanopore sequencing) with short-read sequencing (Fournier et al, 2017). Such high quality assemblies were used as reference genomes for population genomic surveys (Eberlein et al, 2021;Gounot et al, 2020;Serra Colomer, Chailyan, et al, 2020). These population studies revealed that the pangenome is composed of 5,409 ORFs (open reading frames) with 5,106 core and 303 accessory ORFs within the species.…”
Section: Genomic Landscape Of Brettanomyces Bruxellensismentioning
confidence: 99%
See 1 more Smart Citation